SECURING IOT WITH BLOCKCHAIN - K. O. Toka; Y. Dikilitaş; T. Oktay; A. Sayar (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2021)
IoT is becoming ubiquitous in industry, homes, cities, literally in every aspect of our daily lives. Securing IoT-based systems is difficult because of deficiencies in the very nature of IoT devices such as limited battery power, processing, and storage, etc. Blockchain is a new approach used to securely record transactions and offers potential solutions to computer and internet security issues such as confidentiality, integrity, availability, authentication, authorization, and accountability. Blockchain, as a decentralized ledger consisting of interconnected blocks, can remedy most of the security deficiencies of heavily IoT based systems. The Hyperledger Fabric blockchain network used in this study provides confidentiality, data integrity, authentication, and data security for data obtained from IoT devices. Widely used IoT data transfer MQTT protocol is included in the proposed approach. The approach is demonstrated in a simple demo Hyperledger network with simulated IoT devices. The proposed approach is discussed in terms of network security dimensions. Based on the features of the Hyperledger Blockchain network, it is displayed that the IoT security deficiencies can largely be remedied with the proposed approach.